2017
DOI: 10.2217/fvl-2016-0112
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis E Infection in the General Population of Iran: A Systematic Review and Meta-Analysis

Abstract: Aim: Hepatitis E is a form of acute viral hepatitis, which is caused by hepatitis E virus (HEV). The study objective was to evaluate the prevalence of HEV to provide an overall relative frequency in Iran. Methods: In this study, databases such as PubMed and Scopus were searched using the following keywords according to MeSH, “Hepatitis E virus”, “Epidemiology”, “Enzyme-linked immunosorbent assay (ELISA)” and “Iran”. Then studies which had reported prevalence of HEV were selected. Results: We selected 36 resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…58 Another meta-analysis conducted among the general population of Iran reported the overall pooled prevalence of HEV was 9.7%. 59 The estimated seroprevalence of HEV ranged from 0.6% to 52.5% in European countries. 60 Another systematic review of reports of the Brazilian population reported an overall seroprevalence of HEV infection of 6.0%.…”
Section: Discussionmentioning
confidence: 99%
“…58 Another meta-analysis conducted among the general population of Iran reported the overall pooled prevalence of HEV was 9.7%. 59 The estimated seroprevalence of HEV ranged from 0.6% to 52.5% in European countries. 60 Another systematic review of reports of the Brazilian population reported an overall seroprevalence of HEV infection of 6.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Seropositivity in the developed world ranges from 6% in the United States to 39.1% in Southern France, although assays for HEV IgG have reportedly wide ranges of sensitivity[ 156 ]. A 2017 systematic review that analyzed the prevalence of HEV in Iran found an overall positivity rate of 9.7% with varying rates between cities (1.1% in Tehran vs 46.1% in Ahvaz)[ 173 ]. Finally, a recent systematic review and meta-analysis of 56 studies on the seroprevalence of HEV in patients on maintenance hemodialysis (HD) found that the pooled seroprevalence of HEV was 11.13% between 2016 and 2020, which had increased from 6.6% from 1994 to 2000[ 174 ].…”
Section: Hepatitis Ementioning
confidence: 99%
“…It has been estimated that about 20 million people are infected with HEV globally each year, leading to a 3.3 million symptomatic cases and around 44,000 deaths [1]. In developing countries, HEV is mainly transmitted through the consumption of contaminated water and food due to poor hygiene conditions that results in large-scale outbreaks [2,3]. In industrialized countries, transmission usually occurs via alternative routes, like the consumption of undercooked pork as a foodborne zoonosis, which likely contribute to the sporadic cases of acute hepatitis and fulminant hepatic failure, particularly among immunosuppressed individuals [4].…”
Section: Introductionmentioning
confidence: 99%
“…1 In developing countries, HEV is mainly transmitted through the consumption of contaminated water and food due to poor hygiene conditions that result in large-scale outbreaks. 2,3 In industrialized countries, transmission usually occurs via alternative routes, such as the consumption of undercooked pork as a foodborne zoonosis, which likely contributes to the sporadic cases of acute hepatitis and fulminant hepatic failure, particularly among immunosuppressed individuals. 4 Transmission via blood transfusion and blood products, such as packed red blood cells and platelets, has also been demonstrated, especially in developed countries.…”
Section: Introductionmentioning
confidence: 99%